Perempuan dan Perceraian di Masa Pandemi Covid-19: Studi Kasus di Kota Bandung - M. Taufiq, Andi (Medpro, 2024)
This study aims to explore the perspectives of women regarding the increasing divorce rates during the Covid-19 pandemic in Bandung, West Java. The research employs a qualitative approach, utilizing literature reviews and in-depth interviews with women who have experienced divorce during the pandemic. The study reveals that women often choose divorce as the best solution due to moral and ethical violations by their husbands. Post-divorce, these women face multiple pressures, including the dual burden of motherhood and financial independence. The research also indicates that patriarchal values have become more entrenched during the pandemic, further complicating the lives of divorced women. The findings highlight the need for policy interventions to support divorced women and address the deepening patriarchal structures exacerbated by the pandemic. This study provides a unique perspective on the intersection of gender, divorce, and the socio-economic impacts of the Covid-19 pandemic, emphasizing the resilience of women in overcoming systemic challenges.